Exploration of pollen parents for fertility restoration and sterility maintenance behaviour in sunflower (Helianthus annuus L.): EXPLORATION OF POLLEN PARENTS FOR FERTILITY AND STERILITY MAINTENANCE BEHAVIOUR IN SUNFLOWER - SUNILKUMAR SURESH GANIGER; S D NEHRU; H P MEENA; N KARTHIK; C TEJASWAN; SUSHILKUMAR GANIGER; A JAYANTH KUMAR; L SUBHASHCHANDRA SHABANNAVAR (Journal of Oilseeds Research, 2026)
An investigation was carried out to study the sterility maintenance and fertility restoration behaviour of 24 new inbred lines on six CMS lines and also to estimate the combining ability and heterosis by crossing the parents in Line × Tester mating design during early kharif, 2022. The resultant 78 fertile hybrids among the generated 144 hybrids and three check hybrids viz., KBSH 78, KBSH 44 and KBSH 53 were evaluated in Simple lattice design and Parents were evaluated in RCBD design with 2 replications during summer, 2023 for seed yield and its attributing traits. 13 inbred lines viz., GMU-236, GMU-475, GMU-595, GMU-727, GMU-738, GMU-750, GMU-761, GMU-763, GMU-784, GMU-1079, GMU-757, GMU-770 and GMU-759 were recognized as fertility restorers. While, 11 inbred lines GMU-324, GMU-376, GMU-428, GMU-502, GMU-205, GMU-711, GMU-1000, GMU-702, GMU-489, GMU-575 and GMU-557 were identified as sterility maintainers with all six CMS lines.